The content of comments on articles describing suicide: Searching for causes, attitude, myths - Šeibokaitė, Laura; Genutytė, Dovilė (Psichologija, 2015)
Both researchers and society agree that the high rate of suicide is one of the painful problems in Lithuania. Extraordinary accidents of violence, suicide cases attract the media attention. The previous research has revealed that articles describing suicides have an impact on suicide rates. Furthermore, the majority of media articles are moved to the Internet which makes the information easily available. Readers have the possibility to react and write a comment. The problem is that the reactions expressed by commentators, incorrectly describing the suicide cases, can influence readers’ attitudes and affect the stereotypes and beliefs that suicide is a good way of solving problems. The content analysis of comments on articles describing suicide has not yet been performed in Lithuania. The aim of the study is to analyze and describe the content of the comments which were written as a reaction to the articles describing suicide. The purpose is to reveal attitudes toward suicide and a self-murderer, myths about suicide, and attempts to search for the reasons of suicides. The content analysis was performed for 619 comments from the online newspaper www.lrytas.lt. The validity of content categories was assessed with a second rater procedure. The agreement percentage among the raters ranged from 95 to 99 and Cohen’s kappa from 0.7 to 1 throughout the categories. After the first evaluation of the content for this research 385 which were suitable for the further analysis were selected. These comments formulate the attitude towards a person who committed suicide as a coward, emotionally hurt, guilty for this act and mentally deranged. The attitude towards suicide is contradictory: commentators equivalently have expressed both the acceptability and the condemnation of suicide. The common reasons for suicide are seen as a fault of the surroundings, loneliness, and mental disability. Some comments constitute the expressed doubt on suicide as the cause of death and raise the question about homicide alternatively. It can be seen that in comments there exist a few myths about suicide: “only mentally deranged people commit suicide”, “only rich or poor commit suicide”, “to attempt a suicide means the desire to attract attention and compassion”. The results of this study indicate the prevailing negative attitude towards the self-murderer; therefore, they can encounter misunderstanding and even rejection from society. Half of commentators have shown acceptance of suicide and faulty beliefs about it, so this is why more efforts are still needed to educate society to understand the suicide objectively.
Keywords: suicide; self-murderer; attitude; comment; content analysis